PENEGAKAN HUKUM OLEH HAKIM TERHADAP TINDAK PIDANA KORUPSI (Putusan Perkara Korupsi Atas Nama Johny Arifin Siahaan) - Des Boy Rahmat Eli Zega; Muhammad Hamdan; Mahmud Mulyadi; Suhaidi Suhaidi (USU LAW JOURNAL, 2016)
ABSTRACT The District Court’s ruling in imposing sentence on a corrupting defendant does not give any justice to people because corruption has been running rampant and plundering the State’s assets which cause people to become poorer. The process of investigation in the case of Johnny Arifin Siahaan had met the evidence and witness testimony in the hearing so that the defendant should have been imposed maximal sentence, but the ruling of the Medan District Court did not impose maximal sentence. The role of a judge in upholding law in the system of criminal justice is that the judge is active and pays attention to witness and expert testimonies in the hearing. There are at least two valid pieces of evidence and judge’s confidence for a court’s evidence to impose a sentence. In the upholding of law by the judge on the corruption criminal act in the case of Johnny Arifin Siahaan, the Medan District Court’s ruling did not impose maximal sentence, 20 years imprisonment and fine of one billion rupiahs. However, in the appeal to the higher court, the Supreme Court handed down the heavier ruling, compared with the ruling of the Medan District Court and of the Higher Court for corruption criminal act in Medan so that corruptors will get intimidated effect on their extraordinary crime. Keywords: Upholding Law, Judge, Corruption